HAKIKAT DAN TEORI PERKEMBANGAN BAHASA ANAK - Devina; Silvina Noviyanti; Ika Lesmana Putri; Loweni Angelita Siahaan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Language is a medium and means of communication used to convey information to the other person, enabling a smooth conversation. The purpose of this study was to understand the basic understanding of language in children and to explain various theories of child language development. The method used was a descriptive qualitative approach, incorporating a literature review. This approach was used to analyze existing theories in depth based on relevant written materials. The results of the study indicate that children's language is the primary means of communication that develops from birth and goes through various stages of development, from pre-language expression to the ability to master complex language structures. Understanding the nature and theories of child language development is crucial for teachers and parents so they can provide appropriate support at the child's developmental stage. This supports the optimal maturity of children's language skills.